Excellent durability of substoichiometric titanium oxide as a catalyst support for Pd in alkaline direct ethanol fuel cells - Nguyen, Son Truong (2013)
In this study, substoichiometric titanium oxide, TinO2n–1, was compared with carbon black and TiO2 in the role of catalyst supports for Pd in alkaline direct ethanol fuel cell. 10%Pd/C, 10% Pd/commercial TiO2 and 10%Pd/TinO2n–1 catalysts were successfully prepared by a polyol method. The supports and electrocatalysts were characterized by X-ray diffraction (XRD), nitrogen adsorption, electrochemical impedance spectroscopy (EIS), cyclic voltammetry (CV), linear sweep voltammetry (LSV), and chronoamperometry (CA) techniques. Excellent durability was found for TinO2n–1 with holding potential and multiscan tests in N2-purged 1 M KOH solution. Among the three catalysts, Pd/TinO2n–1 showed the best activity and stability for ethanol electrooxidation in alkaline media.